Drama, Politics, and Evolution - McConachie, Bruce. author. aut Link
XVII, 295 p. 1 illus.
Keywords: “A must-read from one of the pioneers of scientific approaches to performance and theater. If, like me, you’re a skeptic about the science of universals, you’ll find a wealth of brilliant readings to challenge and inform you in this innovative book.” --Angus Fletcher, Professor of Story Science at Ohio State’s Project Narrative and author of Wonderworks: The 25 Most Powerful Inventions in the History of Literature (pub.year). “In a brilliant reformulation of evolutionary theory, Bruce McConachie sets up a guiding principle for the unified ways that performance and politics operate in human societies across the centuries. In a series of well-written and carefully argued sections, he argues for the shaping power of evolutionary universals in the stages of human history. As he proclaims, biology and culture are fundamentally intertwined. Now, in our modern times, we are offered a vital understanding of how and why our cultural worlds andsocieties are joined together in the universal controls of evolution.” --Thomas Postlewait, School of Drama, University of Washington, USA. This book outlines the evolution of our political nature over two million years and explores many of the rituals, plays, films, and other performances that gave voice and legitimacy to various political regimes in our species’ history. Our genetic and cultural evolution during the Pleistocene Epoch bestowed a wide range of predispositions on our species that continue to shape the politics we support and the performances we enjoy. The book’s case studies range from an initiation ritual in the Mbendjela tribe in the Congo to a 1947 drama by Bertolt Brecht and include a popular puppet play in Tokugawa Japan. A final section examines the gradual disintegration of social cohesion underlying the rise of polarized politics in the US after 1965, as such films as The Godfather, Independence Day, The DarkKnight Rises, and Joker accelerated the nation’s slide toward authoritarian Trumpism. A historian of performance, Bruce McConachie has written Engaging Audiences (2008), Evolution, Cognition, and Performance (2015), and Theatre Histories: An Introduction (with others, 2006, 2010, and 2016). .